Mobile advertising for the masses - Salz, Peggy (Henry Stewart Talks, 2009)
Marketing with a personal touch, Mobile advertising experiment, Mobile analytics tools, Campaign summary, Mobile social networks, Mobile analytics, Three performance characteristics, Targeting, Recommendation
Archived at 2022/04/11